Clinical outcome of one-third-dose depot triptorelin is the same as half-dose depot triptorelin in the long protocol of controlled ovarian stimulation - Yu Li; Dongzi Yang; Qingxue Zhang (Wolters Kluwer Medknow Publications, 2012)
Objective: Appropriate dosage of the long-acting depot gonadotrophin releasing hormone (GnRH) agonist has not been determined in long protocol for IVF, and one-third-dose depot triptorelin was compared with half-dose in a luteal long protocol of in-vitro fertilization/ intra cytoplasmic sperm injection (IVF/ICSI) treatment in this study. Materials and Methods: This is a prospective, randomized, open clinical trial. 100 patients were randomized into two groups. Group I received one-third-dose (1.25 mg) depot triptorelin. Group II received half-dose (1.87 mg). The clinical and experimental parameters were compared between the two groups. Results: There was no premature luteinizing hormone (LH) surge in both groups. On Day 3-5 of menstrual cycle after down-regulation, fewer patients showed low-level LH (<1.0 IU/L) and estradiol (<30 pg/mL) in group I (P <0.05). There were fewer oocytes retrieved (P =0.086), fewer total embryos and available embryos for cryopreservation in Group I (P <0.05), while good-quality embryo rate was higher in group I (P <0.05). The length and dose of ovarian stimulation was lower in Group I, but not significantly. The clinical pregnancy (52% versus 40%), implantation (48% versus 37.5%), delivery (46% versus 32%), or live birth (42% versus 32%) rates and the abortion (8% versus 20%) rates showed no significant differences. Conclusion: Depot triptorelin 1.25 mg can be successfully used with reduced pituitary suppression and lower cost in a long protocol for in-vitro fertilization.